2013
DOI: 10.5271/sjweh.3383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Danish return-to-work program on long-term sickness absence: results from a randomized controlled trial in three municipalities

Abstract: This is the largest RCT ever conducted on effects of a multiple component return-to-work intervention (coordinated, tailored, and multidisciplinary). The effects of the intervention on duration of sickness absence were remarkably different between the three municipalities examined indicating that contextual factors are of major importance for success or failure of this complex intervention. 47Original article Scand J Work Environ Health. 2014;40(1):47-56. doi:10.5271/sjweh.3383 Effect of the Danish return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 17 publications
0
49
1
Order By: Relevance
“…With a focus on mental disorders, the Danish program on part-time sick leave shows no effect when controlling for unobserved heterogeneity, only program effects for physical illness are present [25]. For three Danish municipalities, the effects of the RTW program are studied [26]. The authors find strong differences between the three municipalities and conclude contextual factors to be important for program success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With a focus on mental disorders, the Danish program on part-time sick leave shows no effect when controlling for unobserved heterogeneity, only program effects for physical illness are present [25]. For three Danish municipalities, the effects of the RTW program are studied [26]. The authors find strong differences between the three municipalities and conclude contextual factors to be important for program success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The review further showed that high-quality studies reported smaller effects than low-quality studies. Later studies have reported no, ambiguous or even negative effects on RTW for sickness beneficiaries [69]. Several studies show that early interventions are preferable, however a better understanding of which specific components of the interventions work for different sickness beneficiaries is clearly needed as interventions may have different effects on different subgroups of participants [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…Poulsen et al suggested that comprehensive multidisciplinary interventions may be more appropriate for sickness beneficiaries with complex reasons for not returning to work than for beneficiaries with less complex reasons [9, 14]. Highly complex reasons may include long duration of sickness absence, problematic social relations at work, poor health and unclear diagnoses based on multiple symptom patterns [1517].…”
Section: Introductionmentioning
confidence: 99%
“…The loss in productivity due to sickness absence is estimated to be €103 billion annually (2). To meet the challenge of work disability, prevention and management of work disability have become a priority in many national health and welfare strategies (3)(4)(5)(6)(7)(8). These strategies are diverse.…”
mentioning
confidence: 99%